Beyond teaching language: Towards terminological primacy in learners’ geometric conceptualisation - Humphrey U. Atebe; Marc Schäfer (Pythagoras, 2010)
This paper reports on a specific aspect of a broader geometry conceptualisation study that sought to explore and explicate learners’ knowledge of basic geometric terminology in selected Nigerian and South African high schools. It is framed by the notion that students’ acquisition of the correct terminology in school geometry is important for their success in the subject. The original study further aimed to determine the relationship that might exist between a learner’s ability in verbal geometry terminology tasks and his/her ability in visual geometry terminology tasks. A total of 144 learners (72 each from South Africa and Nigeria) were selected for the study, using both the stratified and the fish‐bowl sampling techniques. A questionnaire consisting of a sixty‐item multiple‐choice objective test provided the data for the study. An overall percentage mean score of 44,17% obtained in the test indicated that learners in this study had only a limited knowledge of basic geometric terminology. The Nigerian subsample in the study had a weaker understanding of basic geometric terminology than their South African counterparts. Importantly, there were high positive correlations between participants’ ability in verbal geometry terminology tasks and their ability in visual geometry terminology tasks. These results are consistent with those of several earlier studies, and provide a reasonably firm basis for certain recommendations to be made.